1989
DOI: 10.1111/j.1476-5381.1989.tb11848.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peptidases on non‐adrenergic, non‐cholinergic inhibitory responses of tracheal smooth muscle: a comparison with effects on VIP‐ and PHI‐induced relaxation

Abstract: 1 The effects of peptidase enzymes on non-adrenergic, non-cholinergic (NANC) inhibitory responses of guinea-pig trachea to electrical field stimulation (EFS), and on relaxations induced by vasoactive intestinal peptide (VIP) and peptide histidine isoleucine (PHI) have been examined. 2 a-Chymotrypsin reduced both the magnitude and, particularly, the duration of the inhibitory response to EFS, whereas papain reduced only the magnitude. Aprotinin, a peptidase inhibitor prevented the effects of a-chymotrypsin but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…The NANC-induced relaxation of guinea-pig tracheal strips was abolished by tetrodotoxin, as previusly found by Ellis & Farmer (1989a). The effect of co-conotoxin GVIA on NANCinduced relaxations of guinea-pig tracheal smooth muscle was in accord with its effects on responses to cholinergic, noradrenergic and NANC nerve stimulation in a number of tissues (De Luca et al, 1990): responses to stimulation at 1 Hz were abolished and those to stimulation at 5 Hz were reduced.…”
Section: Discussionsupporting
confidence: 61%
“…The NANC-induced relaxation of guinea-pig tracheal strips was abolished by tetrodotoxin, as previusly found by Ellis & Farmer (1989a). The effect of co-conotoxin GVIA on NANCinduced relaxations of guinea-pig tracheal smooth muscle was in accord with its effects on responses to cholinergic, noradrenergic and NANC nerve stimulation in a number of tissues (De Luca et al, 1990): responses to stimulation at 1 Hz were abolished and those to stimulation at 5 Hz were reduced.…”
Section: Discussionsupporting
confidence: 61%
“…a-Chymotrypsin, at a concentration shown to inhibit VIPinduced neural responses in guinea pig trachea (10) and abolish responses to exogenously applied VIP in human trachea ( 12,13 ), had no effect on cholinergic contractile responses to EFS. This suggests that endogenous VIP does not modulate cholinergic transmission in human trachea, exposing a marked difference from the guinea pig airways where both endogenous NO and VIP have been shown to inhibit cholinergic contractile responses ( 14).…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated by the partial inhibition of the i-NANC response by a-chymotrypsin, which abolishes responses to exogenously applied VIP (10), and by L-N0-monomethyl arginine (L-NMMA) and L-NG-nitroarginine methyl ester (L-NAME) (9), which are both potent and selective inhibitors of NO synthesis ( 11 ). In human trachea in vitro VIP is a potent smooth muscle relaxant (2) but no evidence has been found for endogenous VIP mediating the i-NANC response since concentrations of a-chymotrypsin that abolish the response to exogenously applied VIP have no effect on the i-NANC response ( 12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In the guinea-pig, vasoactive intestinal peptide (VIP) and peptide histidine isoleucine (PHI) are strong candidates for at least part of this NANC relaxant response. Ellis & Farmer (1989b) have shown that a-chymotrypsin, in concentrations that selectively abolish responses to high concentrations of exogenous VIP and PHI, reduces inhibitory responses to NANC stimulation by about 35%. This raises the possibility that the remainder of the response is mediated by a nonpeptide substance.…”
mentioning
confidence: 99%